COVID19 & the Public Sphere: Physical responses in Hong Kong and digital responses globally. - Radisich, Emerson (Street Art & Urban Creativity, 2020)
This essay examines the multiplicity of graffiti-based reactions to COVID-19 and its resulting lockdown laws. It utilises Jill Bennett’s work, Practical Aesthetics, to examine the continuation of vigilante graffiti in Hong Kong, as well as the rise of digital street-art globally. I argue that the artform’s many responses indicate the elasticity of graffiti in times of crisis. I also discuss the willingness for communities to either adapt or continue their respective practices of ‘mark-making’ in the public place.